The Antibacterial Effects of Syzygium Cumini Fruit Mouthwash Against Streptococcus mutans as an Agent of Dental Caries - Chismirina, Santi; Andayani, Ridha; Sungkar, Suzanna (International Conference on Multidisciplinary Research, 2020)
AbstractCaries is a disease of the oral cavity characterized by tooth decay due to the dissolution of minerals on the teeth by Streptococcus mutans (S. mutans) attached to the teeth surface. One way to prevent the bacteria from decaying the teeth is by gargling with a mouthwash containing antibacterial ingredients from herbs. The results of our previous research on the Syzygium cumini fruit showed that it was one of the natural ingredients with antibacterial compounds against S. mutans. This study aimed to determine the antibacterialeffects of the Syzygium cumini fruit which was formulated in the form of mouthwash against S. mutans. Syzygium cumini fruit was made into mouthwash preparations which were then tested for stability, including for the organoleptic and antibacterial tests. The results of the organoleptic test showed that the Syzigium cumini fruit mouthwash with formula 4 was the best choice for the mouthwash formula. Antibacterial test results showed that the Syzigium cumini fruit could inhibit the growth of S. mutans, characterized by the formation of a hallo zone with an average diameter of 8 mm. This diameter indicated that the Syzygium cumini fruit mouthwash had moderate inhibition against S. mutans.Keywords: Syzygium cumini, mouthwash, Streptococcus mutans, dental caries